2019
DOI: 10.1186/s12913-019-4534-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer treatment and the risk of cancer death among Aboriginal and non-Aboriginal South Australians: analysis of a matched cohort study

Abstract: BackgroundAboriginal and Torres Strait Islander Australians have poorer cancer outcomes than other Australians. Comparatively little is known of the type and amount of cancer treatment provided to Aboriginal and Torres Strait Islander people and the consequences for cancer survival. This study quantifies the influence of surgical, systemic and radiotherapy treatment on risk of cancer death among matched cohorts of cancer cases and, the comparative exposure of cohorts to these treatments.MethodsCancers register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…It is interesting that Indigenous women in our study had higher utility scores for the ‘early stage invasive throat cancer’ health state at both 12-months and lifetime duration than Indigenous men. This finding is consistent with research by Banham and colleagues on Indigenous South Australians’ cancer treatment [ 34 ], who reported that Indigenous females received more treatment, such as surgeries, systemic therapy and radiotherapy than males, on average. The authors concluded that this was consistent with health-related gender differences observed in the wider Australian population [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is interesting that Indigenous women in our study had higher utility scores for the ‘early stage invasive throat cancer’ health state at both 12-months and lifetime duration than Indigenous men. This finding is consistent with research by Banham and colleagues on Indigenous South Australians’ cancer treatment [ 34 ], who reported that Indigenous females received more treatment, such as surgeries, systemic therapy and radiotherapy than males, on average. The authors concluded that this was consistent with health-related gender differences observed in the wider Australian population [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…These outcomes concur in part with research by Condon et al [ 17 ], who also demonstrated poorer cancer survival amongst Indigenous peoples in the NT, with diagnoses at an advanced stage of the cancer being a contributing factor. Additionally, a previous study from South Australia has flagged issues around availability and access to surgical and systemic treatments amongst Aboriginal cancer patients compared to non-Aboriginal South Australian patients, which further complicated the disadvantages associated with geographic remoteness and advanced stage of disease at diagnosis, compounded by the presence of associated comorbid conditions [ 49 ]. In the present study, owing to the lack of stage-specific data, we are unable to comment on whether a delayed diagnosis was responsible for the poorer survival observed.…”
Section: Discussionmentioning
confidence: 99%
“…Research evidence notes a range of barriers to delivering the best possible quality cancer care to Indigenous people. Barriers include navigating complex cancer treatment and management pathways (often associated with late diagnosis and multiple comorbidities) [ 8 , 9 ], inadequate provision of long-term and continuous care to survivors [ 10 ], and patients’ distrust of the healthcare system [ 11 ]. Delivery of health services in rural/remote areas is another barrier due to the lack of access to services (such as specialist care) and the workforce shortage compared to services available in urban or larger regional cities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%